무선 네트워크에서 스케일러블 비디오의 멀티캐스트 전송을 위한 최적화 연구 (The Graduate School, Ajou University, 2015)
Scalable video coding (SVC) provides an excellent solution because it encodes video into multiple layers with the nested dependency: the base layer encodes the basic video quality and the higher layers, called enhancement layers, refine the video from the lower layers. It means that SVC can provide all the destinations with video data in the multicast video transmission by transmitting different layers depending on various network factors such as available bandwidth of relay nodes, and total network bandwidth. SVC can be more efficient if adaptive modulation and coding (AMC) are jointly utilized in the heterogeneous networks where each node can have different channel status and/or the hardware capability of the receivers. A key issue which utilizes SVC with AMC is how each node selects its modulation and coding scheme (MCS) and transmit (or forward) video with multicast tree under the constraint of available radio resources for multicast services. In other words, a cross-layer scheme which takes effects physical layer, MAC layer, network layer, and application layer into consideration jointly is required. Since their relationship is usually complicated structurally, it is difficult to optimize total profits in terms of video quality. In this dissertation, we study cross-layer optimization design for multicast transmission of the video encoded by SVC with AMC in the wireless networks. First, we design the multicast transmission of scalable video with AMC in the one-hop cellular networks, and extend it to the multi-hop wireless networks to optimize video quality in centralized manner. This approach will be the main topic in this dissertation.
학위논문(박사)--아주대학교 일반대학원 :전자공학과,2015. 2
Keywords: Optimization; Multicast Transmission; Scalable Video Coding